Capaian Penerimaan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Tahun 2018-2022 Di Desa Sukamanah Kabupaten Bekasi - Yani, Yani; Dahuri, Adin (Jurnal Pajak Vokasi (JUPASI), 2023)
Tax payers of Sukamanah Sub District in Bekasi Regency   usually pay their Land and Building of   Rural and Urban Tax (PBB-P2) in three ways, namely paying themseves directly to the bjb Bank of Cikarang, entrusting the payment collectively to   tax collector Officer and online payment using the "Sapa Bekasi" application. Unfortunately, the collection tax revenue during   2018-2022 could not achieve the target. The research is descriptive with qualitative approach. Information relating to the research collected by interviewing tax colletor Officer as well as some residents. Data of PBB-P2 during 2018-2022 obtained from Department of Tax Collection of Sukatani District in Bekasi Regency. The result of the reseach that the achievement of revenue during 2018-2022 ranged from 40,3% to 59,4% or an average achievement of 53,3% per year. These achievements showed that the efforts to collect revenue during that period were ineffective because the rrealization of   revenues did not reach predetermined target. The ineffectiveness of PBB-P2 collection is duet to internal obsracles, such as the number of officers being very disproportionate to the tax payers, as well as external obstacles, such as ineffective the use of "Sapa Bekasi" application and the obedience of tax payers which continue to be encouraged. To increase PBB-P2 revenue for the following years, the Sukamanah Sub District government needs to make improvements, such as collaboratjng with RW and RT administrators, practising the use of "Sapa Bekasi" to pay online and providing an undestanding of the importance of paying tax to financing necessities for community